Investigation of Dry Sliding Wear Behaviour of B4C Particulate Reinforced Mg Matrix Composites - Guleryuz, L. Feray; Ozan, S.; Uzunsoy, D.; Ipek, R. (POLISH ACAD SCIENCES INST PHYSICS, 2013)
Currently some composite materials and related manufacturing methods especially particle reinforced magnesium matrix composites are among important research topics because of their superior properties over monolithic metals. Mg-B4Cp is the commonly used composite material for fabrication of light-weight functional components. Wear behaviour of particle reinforced magnesium matrix composites play critical role for potential application in industries such as automotive and aerospace. In this study, the dry sliding wear behavior of particle reinforced magnesium matrix composites manufactured by powder metallurgy with different amount of B4Cp (3,6,9 wt%) addition is investigated. Wear tests are performed on a pin-on-disk configuration against SAE 1040 steel counter body under constant load and sliding speed. The wear behaviour of particle reinforced magnesium matrix composites was evaluated as a function of B4Cp amount (wt%). After the wear test, worn surface of the samples was examined by scanning electron microscopy for pointing out the wear mechanism. DOI: 10.12693/APhysPolA.123.488
Keywords: Physics